2021
DOI: 10.1093/ageing/afab143
|View full text |Cite
|
Sign up to set email alerts
|

Associations between inflammation, cardiovascular biomarkers and incident frailty: the British Regional Heart Study

Abstract: Introduction cardiovascular disease (CVD) and chronic inflammation are implicated in the development of frailty. Longitudinal analyses of inflammatory markers, biomarkers of cardiac dysfunction and incidence of frailty are limited. Methods in the British Regional Heart Study, 1,225 robust or pre-frail men aged 71–92 years underwent a baseline examination, with questionnaire-based frailty assessment after 3 years. Frailty defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 44 publications
2
17
0
3
Order By: Relevance
“…S5), which is in agreement with previous reports [ 25 , 29 , 31 , 47 , 48 ]. These findings in combination with previous work linking high CVD risk with the onset of frailty (phenotype [ 49 ] and FI [ 50 ]) and subclinical CVD markers [ 51 , 52 ] with frailty further corroborate the intertwined nature of CVD and frailty. Indeed, the relationship between frailty and cardiovascular health may have important clinical implications before a CVD diagnosis.…”
Section: Discussionsupporting
confidence: 83%
“…S5), which is in agreement with previous reports [ 25 , 29 , 31 , 47 , 48 ]. These findings in combination with previous work linking high CVD risk with the onset of frailty (phenotype [ 49 ] and FI [ 50 ]) and subclinical CVD markers [ 51 , 52 ] with frailty further corroborate the intertwined nature of CVD and frailty. Indeed, the relationship between frailty and cardiovascular health may have important clinical implications before a CVD diagnosis.…”
Section: Discussionsupporting
confidence: 83%
“…A prospective study showed that the higher CRP on worsening FI, which was confirmed by our findings [ 25 ]. However, another longitudinal study conducted among older male individuals, reported no significant association between CRP and incident frailty based on the Fried phenotype [ 26 ]. Different measurement tools for frailty are possible explanation, as the Fried phenotype is purely physical, whereas the FI contains more dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In this population, HS-cTn value has demonstrated a prognostic capacity in different clinical scenarios and not only in cardiovascular disease. This HS-cTn capacity moved its use from diagnostic to prognostic tool ( Savonitto et al., 2012 ; Chen et al., 2019 ; Ishigami et al., 2019 ; McKechnieT et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%